2022
DOI: 10.1002/cpe.6834
|View full text |Cite
|
Sign up to set email alerts
|

A survey on effects of adding explanations to recommender systems

Abstract: Explainable recommendations become essential when we need to improve the performance of recommendations and to increase user confidence. Explanations are effective when end users can build a complete and correct mental representation of the inferential process of a recommender system. This paper presents our view on the background regarding the implications of explainability applied to recommender systems. Our work contributes to the better understanding of the concept of explainable recommendation and it offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In recent years, researchers have tried to make the results of these "blackbox" architectures more understandable to human subjects. Surveys from [10], [325] comprehensively cover the latest efforts and emphasize the desirability of robust RSs that can be perceived as reliable and transparent by the users. Some works focus on explicitly modeling latent factors or user profiles [326] and propose the usage of template-based systems to generate user data [253], [327].…”
Section: B Explainable Recommender Systemsmentioning
confidence: 99%
“…In recent years, researchers have tried to make the results of these "blackbox" architectures more understandable to human subjects. Surveys from [10], [325] comprehensively cover the latest efforts and emphasize the desirability of robust RSs that can be perceived as reliable and transparent by the users. Some works focus on explicitly modeling latent factors or user profiles [326] and propose the usage of template-based systems to generate user data [253], [327].…”
Section: B Explainable Recommender Systemsmentioning
confidence: 99%
“…Explainability of Recommender Systems (RS) is an important field which studies methods that learn why a recommendation is suggested by a model for a user [14,15,39]. The explanations provided improve the transparency of the system, by revealing more about the predicted outcome as in how does the model learn personalized preferences for every user [37,45]. Moreover, explanations provided within a RS framework can directly appeal to a user and even influence them to purchase an item if it is very well explained (by providing very detailed information associated with the recommendation) as to why it is recommended to the user [26].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the need to boost people's trust in such systems by allowing them to explain their decision‐making processes in human‐understandable terms via explanations arose. The authors give a survey on the effects of explainable artificial intelligence (XAI) in recommender systems, and a structured presentation of the evaluation of recommender systems in order to comprehend intelligent human evaluation systems and a process for evaluating human‐centered explanations 2 …”
mentioning
confidence: 99%